Proceedings of the 7th International Conference on English Language and Teaching (ICOELT 2019) 2020
DOI: 10.2991/assehr.k.200306.061
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Instagram Platform Toward Junior High School Students’ Speaking Ability

Abstract: The massive used of social media nowadays has caught much attention from the researcher and practitioner in the education field to integrated this advance technology to support teaching and learning process. Instagram can be used as one of interactive tools of learning English, especially for millennial students. This research aims to investigate the effect of using Instagram as learning media toward their speaking ability. This research was conducted by using quasi experimental design. The result of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…Furthermore, as reported by the participants in this study, Instagram motivated them to be able to speak English as fluently as English content creators whose content they watched. This finding was similar to several previous studies (Azlan et al, 2019;Devana & Afifah, 2020;Mahmudah & Ardi, 2020;Pujiati et al, 2019;Wulandari, 2019).…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, as reported by the participants in this study, Instagram motivated them to be able to speak English as fluently as English content creators whose content they watched. This finding was similar to several previous studies (Azlan et al, 2019;Devana & Afifah, 2020;Mahmudah & Ardi, 2020;Pujiati et al, 2019;Wulandari, 2019).…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 93%
“…Wulandari (2019) reported that besides improving learners' speaking proficiency, using Instagram also contributed to enhancing learners' fluency and vocabulary mastery, as well as boosting their self-confidence and motivation. In line with that, several other studies involving Indonesian high school learners also reported the merit of using Instagram in enhancing learners' learning motivation (Mahmudah & Ardi, 2020;Pujiati et al, 2019).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Some results support this study. First, previous research was conducted (Mahmudah & Ardi, 2020) on the use of Instagram to improve speaking skills which has a positive effect on students' speaking skills. The similarity with this study was using the application in learning English.…”
Section: Discussionmentioning
confidence: 99%
“…Education cannot be separated from technological development. Various educational tools and modern educational facilities that support the learning process optimization both at the level of preschool, school, university and also in everyday life (Mahmudah & Ardi, 2020; Nicolaou, Matsiola, & Kalliris, 2019; Nuari & Ardi, 2014). One of them is the presence of media in the learning process.…”
Section: Introductionmentioning
confidence: 99%